The cargo protein MAP17 (PDZK1IP1) regulates the immune microenvironment - García-Heredia, José M. (Oncotarget, 2017)
Inflammation is a complex defensive response activated after various harmful stimuli allowing the clearance of damaged cells and initiating healing and regenerative processes. Chronic, or pathological, inflammation is also one of the causes of neoplastic transformation and cancer development. MAP17 is a cargo protein that transports membrane proteins from the endoplasmic reticulum. Therefore, its overexpression may be linked to an excess of membrane proteins that may be recognized as an unwanted signal, triggering local inflammation. Therefore, we analyzed whether its overexpression is related to an inflammatory phenotype. In this work, we found a correlation between MAP17 expression and inflammatory phenotype in tumors and in other inflammatory diseases such as Crohn's disease, Barrett's esophagus, COPD or psoriasis. MAP17 expression correlated also with the markers of inflammation HLAs, BBS10, HERC2, ADNP and PYCARD. Furthermore, we found that MAP17 expression directly regulates NFAT2 and IL-6 activation, inducing the differentiation of monocytes to dendritic cells and suggesting a causal role of MAP17 in inflammation. Immunohistochemistry confirms local inflammation, mainly CD45(+) cells, at the site of expression of MAP17, at least in tumors, Crohn's and psoriasis. Therefore, our data indicates that the overexpression of the protein MAP17 plays important role in diseases involving chronic inflammation.